Globalization and Maritime Challenges in Western Pacific: US Engagement for Broader Maritime Cooperation with Asian Nations - Wahyu Wardhana (Intermestic: Journal of International Studies, 2016)
The seas and oceans are endless resources and a nation who chose oceans to advance their interest became politically strong and economically prosper. In today globalized economy western Pacific regions are strategic sea lanes that shape international political architecture with increased role in global economic. This essay will describe the usefulness of naval power of world class maritime power especially US Navy and its cooperation with Asian Nations in western Pacific based on theoretical framework from J.R. Hill and Ken Booth in addressing maritime security challenges in western pacific. The conclusion is that The US has been maintaining its naval power in western Pacific for decades by utilized all aspect of sea power in term of hard power as well as soft power to serve as security assurance of maritime trade routes.